Stress-Inducible Expression of an F-box Gene TaFBA1 from Wheat Enhanced the Drought Tolerance in Transgenic Tobacco Plants without Impacting Growth and Development - Kong, Xiangzhu; Zhou, Shumei; Yin, Suhong; Zhao, Zhongxian; Han, Yangyang; Wang, Wei (Frontiers in Plant Science, 2016)
E3 ligase plays an important role in the response to many environment stresses in plants. In our previous study, constitutive overexpression of an F-box protein gene TaFBA1 driven by 35S promoter improved the drought tolerance in transgenic tobacco plants, but the growth and development in transgenic plants was altered in normal conditions. In this study, we used stress-inducible promoter RD29A instead of 35S promoter, as a results, the stress-inducible transgenic tobacco plants exhibit a similar phenotype with WT plants. However, the drought tolerance of the transgenic plants with stress-inducible expressed TaFBA1 was enhanced. The improved drought tolerance of transgenic plants was indicated by their higher seed germination rate and survival rate, greater biomass and photosynthesis than those of WT under water stress, which may be related to their greater water retention capability and osmotic adjustment. Moreover, the transgenic plants accumulated less reactive oxygen species (ROS), kept lower MDA content and membrane leakage under water stress, which may be related to their higher levels of antioxidant enzyme activity and upregulated gene expression of some antioxidant enzymes. These results suggest that stress induced expression of TaFBA1 confers drought tolerance via the improved water retention and antioxidative compete abilibty. Meanwhile, this stress-inducible expression strategy by RD29A promoter can minimize the unexpectable effects by 35S constitutive promoter on phenotypes of the transgenic plants.